Comparative Juridical Analysis Of Witness's Position In Notarial Agreement Making Based On Islamic Law And Public Notary Law (UUJN) - Meta Agulegistin; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
The problem of witnesses has been seen as a significant problem. It requires the reinterpretation of text messages that considered a male witness is equal to two women. The issues raised are: How is the position of witness when making notarial agreement in Islamic law, How is the position of witness when making notarial agreement according to UUJN (Public Notary Law), and What is the similarity and difference of witness position in making notarial agreement according to Islamic law and UUJN. The research method used was Juridical Normative with Regulations approach, Conceptual Approach, and case Approach. Research result found that Firstly, the witness is someone who can give a statement or information that he knows about what the actual events. Another meaning is that a witness is a person who is asked to be present to witness a legal event; Secondly, a witness is a person who can give a definite statement because the person knows the actual event, and even the other meaning of the witness is the person who is asked to attend to witness an event. The person who is asked to be a witness is a qualified person and considered to be well-informed of what he or she is witnessing. And Third, the equation has a purpose for justice and truth can be enforced by the presence of witnesses and the difference Act No.40 of 2014 on the position of a notary. It is originated from the rules of legislation and as evidence, as well as the differences in the conditions specified. On the other hand, Islamic law comes all source of regulations are from Al Quran and As-Sunnah.Keywords: Comparison; Position of Witnesses; Notarial Agreement; Islamic Law; Public Notary Law